Strategi Pemasaran Roti Bakar Jamin Halal Nikmat (JHN) Wangi Madu Studi Kasus Desa Sepuk Tanjung Kacamatan Sebawi Kabupaten Sambas - Susilawati, Irma Fahrizal Butsi Ningsih, (Jurnal Social Economic of Agriculture, 2018)
Bread is an additional food favored by people in Sambas Regency. One of the businesses engaged in making baked bread is "Halal and Delicious Guarantee (Jaminan Halal Nikmat-JHN)" bread of Wangi Madu which is located in Sepuk Tanjung Village, Sebawi District, Sambas Regency. This JHN was founded by Mr. Tiong Nyit Kong in 2010, with a household scale. Production, sales and production leftover from January to March 2017 have decreased every month. One of the factors that causes the production and sales of bread to decline monthly is the reduced purchasing power of consumers against JHN's bread. Therefore, it is necessary to examine how "Marketing Strategy for Baked Bread" Halal Delicious Guarantee of Wangi Madu (Scented Honey) in Sepuk Tanjung Village, Sebawi District, Sambas Regency". In determining the marketing strategy, analysis of internal and external factors was used, then processed using SWOT analysis. From the IFE / EFE analysis, obtained seven strengths with the main strength is to have complete permits and halal certificates with a value of 0,313. Six weaknesses, with its main weakness is that the product is not durable with a value of 0,307. Four opportunities, the biggest opportunity with a value of 0,508 is Consumer Loyalty. Four threats with the main threat value of 0.463 is the rise of online cake traders / sellers. Based on the results of the SWOT analysis, Ten strategies are obtained, namely: introducing current products and expanding the marketing area, developing product variants or adding new products, openness and cooperation, production and sales forecasting, improving product packaging, improving product quality by adding flavors and size, recruiting personnel in certain fields and increasing vehicles, increasing creativity for processing new products that are more in demand by consumers, increasing promotional efforts, creating websites and social media accounts about JHN’s Bread.Keywords : bread, Halal Delicious Guarantee (Jaminan Halal Nikmat-JHN), marketing strategy